Percutaneous cholecystostomy placement in cases non-responsive or otherwise non-operable acute cholecystitis: a retrospective descriptive and outcomes analysis - Gandhi, Karan (Division of General Surgery, 2020)
Purpose of the Study: The primary aim of this research is to demonstrate the safety and efficacy, or lack thereof, of percutaneous cholecystostomy placement as a management option in patients with acute cholecystitis (AC), not suitable for cholecystectomy and not responding to best medical management. The secondary aim of this research is to investigate the feasibility and complexities of interval cholecystectomy in this cohort of patients, with respect to the conversion rate to open, operating time and performing a subtotal cholecystectomy. Background: Acute cholecystitis is a complication of cholelithiasis (gallstones) and one of the most common admission diagnoses in Acute Care Surgery Units. The standard of care, according to the Tokyo Guidelines (1-4), for the management of acute cholecystitis, includes the immediate use of empiric antimicrobial drugs and index-admission laparoscopic cholecystectomy. A (>72 hour) delay between the onset of symptoms and presentation and initiation of medical care, as well as high operative risk patients are the two main reasons for diversion from this protocol of care. In the case of delay, the guidelines suggest the use of interval (six week) cholecystectomy as appropriate care. Index admission cholecystectomy in the setting of delayed presentation has been associated with increased morbidity. As inflammation of the gallbladder progresses, the tissues become more oedematous, with anatomic distortion and therefore increased difficulty in identifying important structural landmarks during LC. This difficulty increases the risk of operative complications, including bleeding and common bile duct injury, the most feared complication of LC. In addition to this distortion, adjacent surrounding organs may be involved in this inflammatory complex, thereby also being placed at risk of injury during dissection. In such circumstances, alternative methods of controlling disease progression may be necessary. 7 According to the Tokyo guidelines (1-4), AC can be classified into three grades of severity, namely mild (grade I), moderate (grade II) and severe (grade III). The grading system takes into account clinical and laboratory parameters, with organ dysfunction representing more advanced disease. Percutaneous cholecystostomy tube placement has been described as a method to achieve sepsis control in patients with severe AC, in which case LC may not be safe, owing to operative and high anaesthetic risk. The use of percutaneous cholecystostomy is well established in critically ill patients with acalculous cholecystitis and its safety and efficacy have been reported in many studies (5-11). Early LC has recently been shown to reduce the rate of major complications as compared to PC, even in high risk patients (15) The management of one subset of patients with acute cholecystitis remains unclear. This group comprises those with delayed presentation, in whom index-admission surgery is not advised, but who subsequently do not respond to best medical therapy. They have traditionally undergone urgent cholecystectomy but suffer higher rates of both morbidity and mortality (12- 14). In the current setting, patients often present with a delay since the onset of symptoms, rendering index-admission cholecystectomy unsafe. This problem is exacerbated by the lack of urgent operating theatre time, often with more urgent cases taking preference, thus delaying operative care beyond what is deemed safe by the Tokyo guidelines. The vast majority of patients are managed by interval cholecystectomy, leaving only the mentioned unresponsive subset. Recent reports have established the safety of the use of percutaneous cholecystostomy tube placement in patient groups that include this subset (severe sepsis, septic shock, local gallbladder rupture, progressive intolerant pain and persistent fever) (5-11).